Chewing Your Way to Understanding - Gupta, Dittika; Lindt, Suzanne F; Moss, Diana (Ohio Journal of School Mathematics, 2017)
Helping upper elementary students to connect mathematical concepts to real world ideas is critical to their long-term conceptual understanding but can be challenging for teachers. This paper explains how 4th and 5th grade students were presented with a real-world mathematical task that was engaging, hands-on, and promoted reasoning and problem solving for students. The paper shares details of the activity, students’ discussions throughout the activity, including: their struggles, their reasoning, and their understanding resulting from their mathematical problem solving from the activity.